Pengaruh Pengawasan dan Disiplin Kerja Karyawan Terhadap Kinerja Karyawan Pada Hotel New Hollywood Pekanbaru - Setia Meilenia Putri; Kasmiruddin Kasmiruddin (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This study aims to determine and analyze the effect of Supervision and Employee Work Discipline on Employee Performance at the New Hollywood Hotel Pekanbaru. This research method is descriptive quantitative by collecting data through free interviews and distributing questionnaires. This study used a sample of 55 respondents using a total sampling technique. The analysis technique uses the regression equation, test the coefficient of determination (R2), and test the hypothesis, namely the t test (partial) and f test (simultaneous). Based on the hypothesis testing, it shows that there is a partially significant effect of Supervision on employee performance with a t count of 5.078 > t table of 2.004 and Employee Work Discipline with t count of 6.225 > t table of 2004. Furthermore, simultaneously Supervision and Employee Work Discipline affect Employee Performance with f count 26.836 > f table 3.175. Among the 2 independent variables that have the strongest influence on Employee Performance is Employee Work Discipline with an R Square value of 0.411. Overall, the results of the simple regression test and multiple regression are well received. Furthermore, the suggestion in this research is that the leadership of the New Hollywood Hotel Pekanbaru improve the quality of supervision and be followed by the application of more objective employee work discipline, and for future researchers to enlarge the sample population with a wide area coverage, it is also suggested to deepen the data analysis and to testing both variables and research indicators, so that it can further sharpen the results that the authors have obtained in this study.